2022
DOI: 10.18662/wlc2021/05
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biomimicry on Visual Design Education

Abstract: The change and increasing diversity in communication tools with globalization have ensured the universal presentation of visual elements shaped by local cultural patterns. Today, design products have turned into a strategic tool for many countries in order to reach higher competitive power. As the visual design industry contributes as an important visual communication and marketing tool for different industries within and outside the creative sector, its role in ensuring sustainability becomes even more import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Studies have shown that hard skills alone are no longer sufficient for survival in the 21st-century world of work [88]. Despite the difference between employers and academics concerning the soft skills needed for employment, the majority of the studies agreed that the importance of non-technical skills cannot be underestimated [29], [89]- [91]. According to the study conducted by Coward [87], non-technical skills are a better predictor of success than technical skills even though, not all soft skills are important for a particular discipline.…”
Section: "They Are Technicians They Must Be Able To Detect Faults And...mentioning
confidence: 99%
“…Studies have shown that hard skills alone are no longer sufficient for survival in the 21st-century world of work [88]. Despite the difference between employers and academics concerning the soft skills needed for employment, the majority of the studies agreed that the importance of non-technical skills cannot be underestimated [29], [89]- [91]. According to the study conducted by Coward [87], non-technical skills are a better predictor of success than technical skills even though, not all soft skills are important for a particular discipline.…”
Section: "They Are Technicians They Must Be Able To Detect Faults And...mentioning
confidence: 99%
“…According to a marketing perspective, the packaging of the product is an extrinsic cue (Chung et al, 2006), and consumers are initially exposed to the product packaging, then they experience the products (Orth & De Marchi, 2007). Manufacturers use product packaging to subliminally communicate with consumers (Thalhammer, 2007) for purposes of brand identity and differentiation, product evaluation (Chung et al, 2006), and consumer brand influence (Bakan & Bakan, 2022;Underwood, 2003). Because packaging reaches most buyers at the crucial moment when they are making a purchase decision.…”
Section: Introductionmentioning
confidence: 99%